2021
DOI: 10.1002/osp4.566
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to mobile‐app‐based dietary self‐monitoring—Impact on weight loss in adults

Abstract: Objectives Greater dietary self‐monitoring adherence is associated with weight loss, however, the dietary self‐monitoring adherence criteria that predict weight loss are unknown. The criteria used to define adherence to dietary self‐monitoring in obesity treatment tend to vary, particularly in studies that include dietary self‐monitoring via mobile applications (apps). The objectives of this study were to (a) determine weight change outcomes related to app‐based dietary self‐monitoring and (b) determine the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…Results revealed that frequency of food tracking was associated with greater weight loss; specifically, a 1% increase in the number of days of food tracking was associated with 0.08% greater weight loss. This is consistent with Payne et al, who reported that a 1% increase in frequency of food tracking was associated with 0.02% greater weight loss [5], and Peterson et al, who showed that high consistency of food tracking improved long-term success in weight management [22]. We extend the literature by reporting the optimum thresholds of food tracking that predicted ≥3%, ≥5%, and ≥10% weight loss at 6 months, which were tracking on 28.5%, 39.4%, and 67.1% of intervention days, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Results revealed that frequency of food tracking was associated with greater weight loss; specifically, a 1% increase in the number of days of food tracking was associated with 0.08% greater weight loss. This is consistent with Payne et al, who reported that a 1% increase in frequency of food tracking was associated with 0.02% greater weight loss [5], and Peterson et al, who showed that high consistency of food tracking improved long-term success in weight management [22]. We extend the literature by reporting the optimum thresholds of food tracking that predicted ≥3%, ≥5%, and ≥10% weight loss at 6 months, which were tracking on 28.5%, 39.4%, and 67.1% of intervention days, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Another study of a 12-week lifestyle intervention found that 68% of participants were consistently tracking in the first week, but this number fell to 21% by 12 weeks [6]. Randomized trials of 6-month lifestyle interventions have reported mean tracking frequency of about 50% of intervention days [5,7], which is far below the daily prescription. In spite of modest adherence to food tracking in lifestyle interventions, it remains a strong predictor of weight loss [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2007–2021, terms such as nutrition ( n = 2294), health ( n = 1734), food ( n = 898), study ( n = 891), and patients ( n = 817) can be observed in Table 4 . Furthermore, recent studies have shown that, in the face of this research, researchers' experience found self-monitoring dietary and physical activity [ 29 , 34 , 45 47 ], healthy diet and lifestyle [ 45 ], and mobile application of dietary self-monitoring [ 46 , 48 – 50 ].…”
Section: Resultsmentioning
confidence: 99%